Local elections 1970 - Westerståhl, Jörgen (University of Gothenburg, 1982)
A survey of citizens in 36 Swedish municipalities in connection with the local general elections 1970. Contains questions regarding choice of party, party identification, service attitudes, knowledge of local politics, media choice, confidence mistrust in local parties and politicians, and a large number of background data of the interviewed persons.

En undersökning genomförd i 36 svenska kommuner under valrörelserna för det lokala allmänna valet 1970. Innehåller frågor om bland annat val av parti, partisympati, attityder, medieval, kunskap om lokal politik och förtroende och misstro till lokala partier och politiker.
Kommunala valrörelser 1970
Keywords: INTERNAL POLITICS; INRIKESPOLITIK; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap